The Journal Illustrada educating for Republic - Thiago Vasconcellos Modenesi; Edilson Fernandes de Sousa; Vilde Gomes de Menezes (Discursos Fotográficos, 2016)
This article aims to identify the educational possibilities contained in press materials in the early years of the Republic of Brazil, from the rise of the Conservative Party, with the end of the Empire and slave regime. Our analysis starts from the hypothesis that the Revista Illustrada collaborated in the way of historicizing the facts to non-literate population, creating a kind of method of transmitting the events with a new look, from the change of habits and of body care benchmarks, good manners and civility.